Mediating role of psychological empowerment in relationships between structural empowerment and organizational culture, and workplace outcomes among academics in Malaysian research universities - Ahadi, Sahar (2012)
The purpose of this study is to examine the mediating effect of psychological empowerment in the relationship between structural empowerment; organizational culture and work related outcomes (job satisfaction and organizational commitment) among academic staffs in research universities in Malaysia. A total of 260 academic staffs from four research universities (UM; UKM; UPM; and USM) participated in this study. Questionnaires were used as instruments to gather data on structural empowerment; organizational culture; psychological empowerment; job satisfaction;and organizational commitment. SPSS and AMOS softwares were utilized for analysis the data. Descriptive statistics (means, standard deviations, and correlation coefficients) were used. The results of confirmatory factor analysis (CFA), which verify the proposed factor structure and test of the construct validity and composite validity, were reported. In conducting confirmatory factor analysis, some items that report lower factor loadings were removed, also, some constructs that cannot appropriately support the construct validity were deleted. Finally, structural model was used to test research hypothesis. The results of structural model showed there was a significant partial mediation on the influence of structural empowerment on organizational commitment through psychological empowerment. And there was a significant partial mediation on the influence of structural empowerment on job satisfaction through psychological empowerment. Also, there was a significant and partial mediation on the influence of clan culture on organizational commitment through psychological empowerment. And there was a significant partial mediation on the influence of clan culture on job satisfaction through psychological empowerment. Therefore, psychological empowerment in the context of higher education organization specially in research universities consider as an important factor, which may improve work outcomes’ behaviors of academic staff. If leaders of higher education can improve the psychological empowerment of academic staff in research universities, this will help them achieve greater commitment and job satisfaction among academics.